PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TPS (THINK PAIR SHARE) TERHADAP HASIL BELAJAR BIOLOGI SMA - Chici Anugrah; Ristiano; Rahmadhani Fitri; Ganda Hijrah Selaras (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Most people think of biology as a subject that is difficult to tackle with cellular stuff and contains an impressive amount of rote material. This reduces the enthusiasm of students to attend biology classes. This study aims to determine the effect of applying the TPS (Think Pair Share) learning model on cognitive learning outcomes in high school Biology. This research uses meta-analytic review articles with literature review-based studies in biology using 5 research articles from Indonesian journals that contain data collection using the Google Scholar database. The results showed that the Think Pair Share Think (TPS) cooperative learning model could improve students' biology learning outcomes.